Phylogeny of Davallia (Davalliaceae) from Sumatra and Mentawai Islands, Indonesia: evidence from trnL-F Intergenic Spacer - MILDAWATI MILDAWATI; SOBIR SOBIR; SULISTIJORINI SULISTIJORINI; TATIK CHIKMAWATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mildawati, Sobir, Sulistijorini, Chikmawati T. 2023. Phylogeny of Davallia (Davalliaceae) from Sumatra and Mentawai Islands, Indonesia: evidence from trnL-F Intergenic Spacer. Biodiversitas 24: 4589-4596. Davallia is a member of the family Davalliaceae, which has a wide distribution in the Malesia region. The classification of this genus based on morphological and molecular data shows differences that cause the relationship among species to be debated until now. This study aimed to examine the phylogeny of Davallia from Sumatra and Mentawai Islands, Indonesia based on trnL-F intergenic spacer (IGS) sequence data. A total of 26 accessions representing 10 Davallia species were selected as ingroup and Oleandra articulata (Sw.) C.Presl as an outgroup was downloaded from Gen-Bank (accession number KF667613.1). Data analysis using the Maximum Parsimony (MP) method confirmed Davallia into 2 clades with divided into 7 subclades. Results showed that trnL-F IGS sequence as a non-coding gene explains the grouping species in Davallia. trnL-F IGS sequence can estimate species identity caused by changes in nucleotide bases from mutation. The MP analysis showed each species was resolved as monophyletic. Based on the phylogenetic tree, the longest branching was found in D. corniculata, suggesting that this species is the most primitive in the genus of Davallia in this region. Thus, the trnL-F marker effectively showed the relationship among species in Davallia in Sumatra and Mentawai Islands.